Comparison of in-situ versus ex-situ delivery of polyethylenimine-BMP-2 polyplexes for rat calvarial defect repair via intraoperative bioprinting. (1st January 2023) - Moncal, Kazim K; Yeo, Miji; Celik, Nazmiye; Acri, Timothy M; Rizk, Elias; Wee, Hwabok; Lewis, Gregory S; Salem, Aliasger K; Ozbolat, Ibrahim T
Abstract: Gene therapeutic applications combined with bio- and nano-materials have been used to address current shortcomings in bone tissue engineering due to their feasibility, safety and potential capability for clinical translation. Delivery of non-viral vectors can be altered using gene-activated matrices to improve their efficacy to repair bone defects. Ex-situ and in-situ delivery strategies are the most used methods for bone therapy, which have never been directly compared for their potency to repair critical-sized bone defects. In this regard, we first time explore the delivery of polyethylenimine (PEI) complexed plasmid DNA encoding bone morphogenetic protein-2 (PEI-pBMP-2) using the two delivery strategies, ex-situ and in-situ delivery. To realize these gene delivery strategies, we employed intraoperative bioprinting (IOB), enabling us to 3D bioprint bone tissue constructs directly into defect sites in a surgical setting. Here, we demonstrated IOB of an osteogenic bioink loaded with PEI-pBMP-2 for the in-situ delivery approach, and PEI-pBMP-2 transfected rat bone marrow mesenchymal stem cells laden bioink for the ex-situ delivery approach as alternative delivery strategies. We found that in-situ delivery of PEI-pBMP-2 significantly improved bone tissue formation compared to ex-situ delivery. Despite debates amongst individual advantages and disadvantages of ex-situ and in-situ delivery strategies, our results ruled in favor of the in-situ delivery strategy, which could be desirable to use for future clinical applications.